Synthesis, crystal structure and Hirshfeld surface analysis of 5-methyl-2-[(1,3-thiazol-2-yl)sulfanyl]-1,3,4-thiadiazole - Kinshakova, Ekaterina; Torambetov, Batirbay; Bharty, Manoj K.; Atashov, Aziz; Rasulov, Abdusamat; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Acta Crystallographica Section E Crystallographic Communications, 2025)
The title compound, C<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">6H<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">5N<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">3S<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">3, consists of two biologically relevant heterocyclic units, suggesting potential biological activity and possible use as a ligand in metal complexation. The compound crystallizes in the monoclinic space group P2<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">1/c and features non-classical intermolecular C—H⋯N hydrogen bonds, along with π–π stacking interactions that contribute to the crystal cohesion. Hirshfeld surface analysis highlights significant intermolecular interactions including, among others, N⋯H/H⋯N, S⋯H/H⋯S, and S⋯C/C⋯S contacts.

Synthesis, crystal structure, Hirshfeld surface analysis and DFT calculations of the coordination compound tetraaquabis2-[(5-methyl-1,3,4-thiadiazol-2-yl)sulfanyl]acetato-κOcobalt(II) - Kinshakova, Ekaterina; Torambetov, Batirbay; Kaur, Simranjeet; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E Crystallographic Communications, 2025)
A relatively strong hydrogen bond between one of the water molecules and the non-coordinating carboxylate O atom consolidates the conformation. In the crystal, intermolecular hydrogen bonds lead to the formation of a complex tri-periodic structure. Hirshfeld surface analysis revealed that 30.1% of the intermolecular interactions are from H⋯H contacts and 20.8% are from N⋯H/H⋯N contacts. DFT calculations were performed to assess the stability and chemical reactivity of the compound by determining the energy differences between the HOMO and LUMO.